THE DEVELOPMENT OF "ACCESS" ANDROID BASED LEARNING MEDIA IN THE ACCOUNTING CYCLE MATERIAL - Agata Bonfilia Hanny; Muhammad Andryzal Fajar (Jurnal Pendidikan Akuntansi Indonesia, 2021)
This research is intended to produce "Access" Android Based Learning Media in The Service Company Accounting Cycle. This is a Research and Development type of research that includes four phases, namely: Analysis, Design, Development, and Implementation. The feasibility of the learning media was assessed by material expert, media expert, accounting learning practitioner and students, using questionnaires. The quantitative research data were analyzed using the quantitative-descriptive analysis technique. The final product of this research is a learning media in the form of Android Application. The media includes material, questions, and game. The results of this research indicate; (1) “Access” android-based learning media development through 5 phases, they were: Analysis, Design, Development, and Implementation. (2) The development of “Access” android based learning media on expert evaluation: a) Material expert got score 3,66 with “Very feasible” category, b) Media expert got score 2,89 with category “Feasible”, c) Accounting learning practitioner got score 3,79 with the category “Very Feasible”. (3) Students assessment to media got average score 3,46 with the category “Very feasible”. The developed “Access” android-based learning media shows that it is very feasible as the learning media.